A Challenge within Macromarketing: Global Disasters. (September 2019) - Iacobucci, Dawn
This essay reflects on the burgeoning literature by marketing scholars in addressing various aspects of global disasters, from both natural and man-made causes. Marketing scholarship into elements of disaster management may be an example of a phenomenon in the "macro cross" posited by Peterson (2016). Disaster events are numerous and striking, with most comprising some element of consumption, hence, marketers might be well-poised to contribute to preparedness and recovery.